Relationship between obesity and musculoskeletal disorders: A scope review protocol (Research, Society and Development, 2021)
Obesity is considered a public health problem and the review of the scientific literature allows the observation of several changes in the musculoskeletal system associated with this disease. The objective of this study is to describe the relationship between these changes in obese children and adults. This article is a scope review protocol, a study methodology based on the structure described by Arksey and O'Malley. The study protocol followed the recommendations from the Preferred Reporting Items for Systematic reviews and Meta-Analyzes extension for Scoping Reviews (PRISMA-ScR) Checklis.  It will be conducted in five stages: a) elaboration of the research question; b) identification of relevant studies; c) selection of studies; d) data extraction; e) summary of the results. The study aims to correlate musculoskeletal disorders in obesity, in different stages of bone maturation, which are less studied, in order to provide scientific evidence to health care professionals involved in the multidisciplinary treatment of this chronic disease.